INTEGRASI HADIS DAN TASAWUF DALAM PEMIKIRAN SUFYAN ATS-TSAURI - Edi Massolihin; Ahmad Roziki (AL ISNAD: Journal of Indonesian Hadith Studies, 2025)
This article examines the unique phenomenon in second-century Hijri Islamic history: the integration of hadith expertise and Sufism in the figure of Sufyan Ats-Tsauri (97-161 H/716-778 M). Known as Amirul Mukminin fil Hadith, Ats-Tsauri demonstrated that hadith scholarly precision could harmoniously coexist with Sufi spiritual depth. Using a historical-biographical approach, this research analyzes Ats-Tsauri's intellectual and spiritual journey and his influence on Islamic scholarship. The study finds that Ats-Tsauri's contributions extended beyond his hadith works like Al-Jami' Al-Kabir and Al-Jami' As-Saghir to include an integrative model combining Islam's outward and inward dimensions. His distinctive approach maintained balance between methodological rigor in hadith transmission and profound spiritual experience. The research reveals how Ats-Tsauri built his Sufi foundation on solid hadith principles, showing that authentic Islamic spirituality must be grounded in the Prophetic Sunnah. His intellectual legacy establishes a paradigm demonstrating that the dichotomy between hadith scholars and Sufis is unnecessary. This research addresses: What are the characteristics of Sufyan Ats-Tsauri's hadith, Sufism, and theological thought in the context of Islamic knowledge integration? These findings contribute significantly to understanding knowledge integration in Islam while offering an alternative model for contemporary Islamic studies that often become trapped in overly narrow specialization.